PEMBUATAN APLIKASI DIGITAL LIBRARY DI JURUSAN ILMU KOMPUTER UNIVERSITAS NUSA CENDANA BERBASIS WEB - Farmi S Radjatadoe; Dony M Sihotang; Meiton Boru (Universitas Nusa Cendana, 2017)
The development of digital library (digital library) can not be separated from the development of information technology. Digital library (digital library) is built on web technology, which allows accessing collections of digital files by users, whenever and wherever the user's position is through the internet. Computer Science Department Library had information stored physical forms such as books, theses, journals and various other scientific work is a collection of 115 pieces. However, management is still closed in the sense just for the students and lecturers so that still untapped by many. Application is a web-based digital library using a global network of media, namely the Internet. Making these applications using the programming language PHP and MySQL as database. For the development of applications using the System Development Life Cycle (SDLC) Waterfall models. Based on black box testing can be seen that in running applications run well because the test result consistent with the result expected by the internal user and based on internal testing results of questionnaire use applications, the largest percentage in the results of a questionnaire on the aspects of software engineering that is 66,25 % (response 5 = very good), on the aspects of functionality that is 67,5 % (response 5 = very good) and on the aspects of visual communication that is 77,5 % (response 5 = very good). With the use of a questionnaire testing the application using Likert’s Summated Rating Method (LSR), the overall total score (1000) on the interpretation of LSR, program is considered successful.